Greek durative verbs with the nasal infix and suffix - Witczak, Krzysztof Tomasz (Array, 2020)
The Indo-European nasal infix presents have not been explained so far from the semantic point of view. The present author argues that the infix *-n(e)- originally expressed the feature of durativity. Due to the diachronic externalization of inflection this nasal morpheme later evolved into a suffix added to the verbal root. Numerous durative verbs with the nasal marker -an- are attested as early as the 2nd millennium BCE in the Anatolian languages; cf. Hittite iy-ann-a/i- ‘to march, go a long distance’, Palaic iyannnai ‘he marches (a long distance)’ vs. Hitt. i- ‘to go’, Luw. i-, Hier.Luw. i-, Lat. eō, īre, Lith. eĩti, OChSl. iti ‘id.’ (<PIE. *h1ei- ‘to go’). The durative verbs in question, as well as the related nouns with the durative suffix *-ano-, also appear in other Indo-European languages, cf. Toch. B yaneṃ ‘they walk, go (for a long time)’. Numerous Greek present forms (e.g. ἁνδάνω, θιγγάνω, λαμβάνω, λανθάνω, λιμπάνω, μανθάνω, πυνθάνομαι and so on) document the same nasal morpheme not only infixed into a verbal root, but also in the form of the suffix -αν-. It is to be explained as the effect of the diachronic externalization of the durative (nasal) morpheme. The Greek verbal forms with the nasal infix and the nasal suffix should be treated as intermediate or hybrid. Newer forms (indicating the durativity of the action) in Greek contain only a nasal suffix (e.g. αὐξάνω, ἱζάνω, ἰσχάνω, κευθάνω, ληθάνω, οἰδάνω, ῥοφάνω).